A research methodology for characterising dairy product consumption systems - Mullins, G.; Rey, B.; Nokoe, S.; Shapiro, Barry I. (International Livestock Centre for Africa, 1994)
This document on characterisation methodology specifically refers to the dairy consumption systems. The methodology developed and presented herein aims at guiding the activities of scientists who wish to investigate the dairy consumption systems at or around a specific site. Some characterisation of dairy product consumption has been conducted at most ILCA zonal sites. Pursued by different scientists at different times and places, a variety of methodological approaches have been employed in conducting these studies. This document is based upon ILCA's experiences at its zonal sites and incorporates the methodological lessons learned in the course of the studies. The steps that have been followed in constructing the conceptual framework instruments and in specifying the analytical methods are outlined. Data collected and analysed following this format will allow drawing conclusions about a particular location and its consumption system. It will also facilitate planning future research and development activities.